Incidencia de la pliometría en patadas altas, medias y bajas en deportistas de artes marciales mixtas de la cuidad de Riobamba. - Mayorga López, Marco Fausto (2022)
For this investigation a study was conducted to determine the impact of a plyometric program and how this will help the improvement and strength of low, medium and high kicks, it is a quasi-experimental research in which 11 mixed martial arts athletes from the Striking Lab academy in the city of Riobamba participated, They were given a pre-test using the research instrument My Jump 2, which is a mobile application that measures jump height, strength, speed, speed, power, contact time, strength profile and speed, which measures their strength levels in the lower limbs. After the application of the plyometric program, the post-test was taken, showing favorable results in the research, such as the increase in strength, power and height of the athletes. Therefore, it is concluded that well guided training and with new forms of application in this case plyometric training helps significantly to the strength in lower limbs and also to the strength in low, medium and high kicks. Plyometrics is a training method which helps to enhance the physical capabilities of athletes regardless of the sport in which this training method is used.